2016
DOI: 10.1155/2016/2957354
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Protects against Glutamate‐Induced Excitotoxicity via Activating SIRT1‐Dependent PGC‐1α Expression in HT22 Hippocampal Neurons

Abstract: Glutamate- (Glu-) induced excitotoxicity plays a critical role in stroke. This study aimed to investigate the effects of APN on Glu-induced injury in HT22 neurons. HT22 neurons were treated with Glu in the absence or the presence of an APN peptide. Cell viability was assessed using the MTT assay, while cell apoptosis was evaluated using TUNEL staining. Levels of LDH, MDA, SOD, and GSH-Px were detected using the respective kits, and ROS levels were detected using dichlorofluorescein diacetate. Western blot was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…The present study indicated that aPn increased the expression of lc3ii and Beclin-1 in the brain tissue simultaneously with inhibition of caspase-3 activation. To the best of the authors' knowledge, the present study is the first to demonstrate that aPn protected the neuron from Gcir injury-induced excessive apoptosis following ca-cPr by promoting autophagy, although Yue et al (41) reported that aPn increases the expression of lc3ii and Beclin-1 in the skeletal muscle of diabetic mice to reduce apoptotic cells in a diabetic mouse model. The mechanisms of how aPn regulates the crosstalk between apoptosis and autophagy in brain tissues injured by Gcir following ca-cPr remain to be elucidated.…”
Section: Discussionmentioning
confidence: 49%
“…The present study indicated that aPn increased the expression of lc3ii and Beclin-1 in the brain tissue simultaneously with inhibition of caspase-3 activation. To the best of the authors' knowledge, the present study is the first to demonstrate that aPn protected the neuron from Gcir injury-induced excessive apoptosis following ca-cPr by promoting autophagy, although Yue et al (41) reported that aPn increases the expression of lc3ii and Beclin-1 in the skeletal muscle of diabetic mice to reduce apoptotic cells in a diabetic mouse model. The mechanisms of how aPn regulates the crosstalk between apoptosis and autophagy in brain tissues injured by Gcir following ca-cPr remain to be elucidated.…”
Section: Discussionmentioning
confidence: 49%
“…Similarly, adiponectin has been shown to have a neuroprotective effect by inhibiting NMDA-mediated excitotoxicity [ 128 ]. In addition, adiponectin and memantine play a protective role in glutamate-induced excitotoxicity (shown in both animal/in-vitro models) [ 129 , 130 ]. Furthermore, memantine also has the ability to attenuate insulin resistance and improve brain function in high-fat diet-induced models.…”
Section: Adiponectin-associated Therapeutic Strategy Against Ad Inmentioning
confidence: 99%
“…Both SIRT1 and PGC‐1α are involved in the mitochondrial biogenesis and inflammatory processes. It has been reported that reduction of SIRT1 activity results in inhibition of PGC‐1α . In human GCs, the exact roles of resveratrol in terms of its cytoprotective effects and ability to improve mitochondrial quantity in a hypoxic condition remain unclear.…”
Section: Introductionmentioning
confidence: 99%